2005
DOI: 10.1111/j.1600-0501.2005.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometry and micro‐computed tomography of bone augmentation under a titanium membrane

Abstract: The total bone volume measured underneath a membrane using the micro-CT when compared with histological sections remained within a 16% error. This is because of the scattering effect of the metallic membrane and the impossibility to distinguish newly formed bone from the original skull bone on the micro-CT images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 11 publications
6
35
2
Order By: Relevance
“…This result was similar to previous studies. Maréchal et al [19] reported a strong correlation between micro-CT and serial histological sections of bone augmentation under a titanium barrier membrane with r 2 =0.072. Umoh et al [20] compared the histological assessments and in vivo micro-CT images in a rat calvarial model and also observed a high correlation between both examinations with r 2 =0.70.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to previous studies. Maréchal et al [19] reported a strong correlation between micro-CT and serial histological sections of bone augmentation under a titanium barrier membrane with r 2 =0.072. Umoh et al [20] compared the histological assessments and in vivo micro-CT images in a rat calvarial model and also observed a high correlation between both examinations with r 2 =0.70.…”
Section: Discussionmentioning
confidence: 99%
“…Direct comparison of micro-CT images with histology in rat confirmed good agreement with respect to fine bone detail. Marechal et al (16) used micro-CT and histological sections to examine the extent of bone augmentation underneath an occlusive membrane; the results were highly correlated. Umoh et al (17) compared histological assessments and in vivo micro-CT images and observed consistent patterns of bone formation in both.…”
Section: Discussionmentioning
confidence: 99%
“…However, when imaging the ECM or tissue growth in metallic scaffolds or around implants, additional caution has to be taken during image analysis as metal artifacts 20,21 can significantly influence the accuracy of the quantification of the newly formed ECM or tissue volume. 22,23 Several studies have shown that when using phase-contrast imaging, in most cases only available by synchrotron radiation, the nonmineralized ECM formed in vitro in 3D TE constructs can be visualized. [24][25][26] However, routine access to systems allowing phase-contrast imaging is limited and there are restrictions on the sample specifications.…”
Section: Introductionmentioning
confidence: 99%